RETURNED FOOT EXTERIOR CHORD BROOCHES MADE OF A SINGLE METAL PIECE (TYPE ALMGREN 158) RECENTLY DISCOVERED IN THE WESTERN PLAIN OF ROMANIA. - Vitalie Bârcă (Journal of Ancient History and Archaeology, 2014)
This study, without aiming at exhaustiveness, attempts, based on returned foot exterior chord brooches made of a single metal pieces (type Almgren 158) discovered in 2010 following the rescue archaeological excavations performed as a result of the construction of the Arad-Timişoara Highway, respectively section Arad-Seceani, in a series of Sarmatian graves of the cemetery investigated at Hunedoara Timișană, Șagu commune, Arad county, to analyse the brooches in this type discovered in the western territories of Romania. The author examines the four specimens at Hunedoara Timișană within a broader context and concludes that similar brooches in both the Barbarian and Roman environments, where they are imports, date mainly to the chronological interval comprised between the last two decades of the 2nd c. – early 4th c. AD (stages C1a-C2). The analysis of the graves in the cemetery showed that the graves where returned foot exterior chord brooches were found date sometime in the chronological interval comprised between the end of the 2nd c. AD and the third quarter of the 3rd c. AD. Moreover, the author notes that the distribution area of this brooch type is mainly the Barbarian world of German origin (the Przeworsk culture environment) or that in constant contact with the latter. Based on the analysis of the distribution area of the Almgren 158 type brooches it was concluded they originate in the Przeworsk culture environment from where they disseminated in the neighbouring south and south-east cultural environments. Last but not least, the author reaches the conclusion that brooches of the type were assumed by the Sarmatians in the Pannonian Plain from the German populations (most likely the Vandals) living in the northern vicinity of the area they inhabited. Another conclusion is that such returned foot exterior chord brooches are lacking from the north and north-west Pontic areas, including the Chernyakhov area. Finally, the author argues that returned foot exterior chord brooches are artifacts that evidence, beside other categories of German origin artifacts (for instance the headknob brooches, exterior chord and solid catchplate), the existence of contacts and cultural and economic interferences between various populations from territories in the east of Central Europe, accurately defining the movement direction of German population groups starting with the last third of the 2nd c. AD (C1a), in the Marcomannic wars’ aftermath as well as the role they played in this region during the 2nd – 4th c. AD. Based on above brooches and other artifact categories in the graves at Hunedoara Timișană, the author concludes the cemetery dates to the chronological interval comprised between the end of the 2nd c. and the third quarter of the 3rd c. AD.